Charles Bonnet syndrome versus Occipital Epilepsy, a diagnostic challenge - Zhuzhuni, Holta; Nazaret, Andrea; Iodice, Lanfranco; Celletti, Saverio; Anticoli, Sabrina; Di Cioccio, Luigi; Cipolla, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Charles Bonnet Syndrome (CBS) is a disorder with visual deficit and complex recurrent visual hallucination in conscious patients, described for the first time by Charles Bonnet. It has been found in association with variable pathologic conditions of the eyes, central visual pathways and occipital lobe. Occipital lobe lesion is an important cause of visual field deficit associated with elementary simple hallucinations, whereas complex hallucinations are related to occipitotemporal and occipitoparietal visual association neocortex damage.